Sensitivity Analysis and Numerical Simulation Study on Main Controlling Factors of Surface Movement and Deformation in Strip Filling Mining under Thick Unconsolidated Layers. (30th June 2021) - Sun, Dequan; Wu, Quanlin; Li, Xiaoyan; Zhang, Zhaomin; Xu, Xiaotian; Li, Yang; Wu, Quansen
Abstract : In many mining areas, there is a lot of pressed coal under buildings, railways, and water bodies, and there are geological conditions of thick unconsolidated layers, so the surface subsidence has certain particularity. The key to solve the problem of pressed coal is the control technology of surface subsidence. The development of strip filling technology provides a kind of economical and effective surface subsidence control technology. With the passage of time, the natural weathering, flow, and fracture of some coal pillars may lead to the instability and failure of some coal pillars. Therefore, the selection of filling parameters plays an important role in the stability of coal pillars. In order to study the influence factors of surface movement and deformation, considering the influence factors of filling rate, key layer thickness, filling body strength, and unconsolidated layer thickness, FLAC 3D was used to simulate the surface movement deformation, and the orthogonal test method was used to analyze the simulation results, and the sensitivity of the main control factors affecting the surface deformation affected by strip filling mining was studied. The results show that the order of importance of the four factors on the four surface movement and deformation parameters is filling rate > key layer thickness > filling body strength > unconsolidated layer thickness. The influence of these four factors on the surface movement and deformation parameters is gradually decreasing, but the influence degree of different factors has drawn a certain gradient.